A study on the clinical efficacy and safety of repetitive transcranial magnetic stimulation combined with transcranial direct current stimulation in adolescent depression - Zhang, Qingyu; Yang, Lu; Zhu, Zhenzhen; Wang, Guanjun; Hu, Jieqiong; Tong, Maoqing; Lou, Zhongze; Chai, Ying; Ye, Yun; Chen, Yan; Wang, Lanlan; Wang, Kuilai; et al. (Frontiers in Psychiatry, 2025)
BackgroundThe prevalence of adolescent depression has been steadily rising, while the effectiveness of existing treatments remains limited, highlighting the urgent need for novel therapeutic strategies.ObjectiveTo evaluate the efficacy and safety of combining repetitive transcranial magnetic stimulation (rTMS) with transcranial direct current stimulation (tDCS) in treating adolescent depression.MethodsThis was a prospective, randomized, parallel-group controlled trial. A total of 260 hospitalized adolescents diagnosed with major depressive disorder (MDD) were enrolled and randomly assigned to one of four groups: G1 (medication only), G2 (medication + tDCS), G3 (medication + rTMS), and G4 (medication + combined tDCS and rTMS). Clinical assessments were conducted at baseline and after 4 weeks by trained evaluators blinded to group allocation. The primary efficacy outcome was the reduction rate in HAMD-17 scores. Secondary outcomes included changes in HAMA and PSQI scores.ResultsBoth the G3 and G4 groups showed significant improvements in depressive symptoms compared to G1 (p < 0.05 and p < 0.01, respectively), with anxiety symptoms also showing significant improvement (p < 0.05). However, no significant differences were observed for sleep quality improvement (p > 0.05). Regression analysis indicated that baseline depression severity and illness duration were key predictors of treatment response (p < 0.001). All interventions were well tolerated, and no serious adverse events were reported.ConclusionThe combination of rTMS and tDCS demonstrates superior efficacy over pharmacotherapy alone in reducing depressive symptoms in adolescents, with a favorable safety profile.